2014
DOI: 10.1149/2.0181502jss
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Ni2+-, Co2+-, and Mn2+-doped ZnS Nanoparticles Synthesized Using Reverse Micelle Method

Abstract: Zn 1−x Y x S (x = 0.00, 0.02, 0.04, 0.06, 0.08, and 0.10) was prepared by reverse micelle method using sodium bis(2ethylhexyl)sulfosuccinate (AOT) as surfactant; Y refers to Ni 2+ , Co 2+ , and Mn 2+ ions. The effects of ion doping on the optical characterization, structure, and morphology of ZnS were investigated using ultraviolet-visible (UV-vis) spectroscopy, photoluminescence (PL) spectrophotometry, Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), field-emission scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It can be observed that there are two weak bands around 485 and 1380.2 cm −1 that are due to Ag-O [ 42 ]. On the other hand, it can be seen that ZnS shares a peak with CA at 1027.16 cm −1 [ 43 ]. The two weak peaks at 485 and 677.2 are attributed to Zn-S cm −1 [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that there are two weak bands around 485 and 1380.2 cm −1 that are due to Ag-O [ 42 ]. On the other hand, it can be seen that ZnS shares a peak with CA at 1027.16 cm −1 [ 43 ]. The two weak peaks at 485 and 677.2 are attributed to Zn-S cm −1 [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it can be seen that ZnS shares a peak with CA at 1027.16 cm −1 [ 43 ]. The two weak peaks at 485 and 677.2 are attributed to Zn-S cm −1 [ 43 ]. The peaks of ZnS and Ag 2 O could be due to their very low concentrations compared to CA film.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, when Mn 2+ is incorporated into ZnS, there are Mn-S bonds appeared in Mn 2+ :ZnS host. Compared with that of Zn-S (2.341 Å), the bond length of Mn-S (2.431 Å) is longer 41 42 , thus, it is easier for the adsorbed oxygen molecules to draw electrons from Mn 2+ :ZnS NWs ( Fig. 5b ), which is beneficial to increase the charge depletion layer depth and obtain a high response.…”
Section: Resultsmentioning
confidence: 99%
“…The standard IR spectrum of Sigma Aldrich was used along with the literature values to analyze absorption peaks. [33][34][35][36][37] Fig. 8(a) represents spectra for uncapped samples ZS0, ZC0, and ZA0.…”
Section: Fourier Transform-infrared Spectroscopy (Ftir)mentioning
confidence: 99%